Rare case of ovarian pregnancy - Kori, Archana; Bhati, Balgopal Singh; Patidar, Arti; Bhati, Indra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Ovarian pregnancy is one of the rarest ektopos i.e. out of place pregnancy. Here we present a case of ectopic pregnancy which was misdiagnosed as tubal ectopic but finally came out as ovarian pregnancy after confirmation with surgery and histopathology.